Hydrogel nanofibers from carboxymethyl sago pulp and its controlled release studies as a methylene blue drug carrier - Mohd Kanafi, Nafeesa; Abdul Rahman, Norizah; Rosdi, Nurul Husna; Bahruji, Hasliza; Maarof, Hasmerya (MDPI, 2019)
The potential use of carboxymethyl sago pulp (CMSP) extracted from sago waste for producing hydrogel nanofibers was investigated as a methylene blue drug carrier. Sago pulp was chemically modified via carboxymethylation reaction to form carboxymethyl sago pulp (CMSP) and subsequently used to produce nanofibers using the electrospinning method with the addition of poly(ethylene oxide) (PEO). The CMSP nanofibers were further treated with citric acid to form cross-linked hydrogel. Studies on the percentage of swelling following the variation of citric acid concentrations and curing temperature showed that 89.20 ± 0.42% of methylene blue (MB) was loaded onto CMSP hydrogel nanofibers with the percentage of swelling 4366 ± 975%. Meanwhile, methylene blue controlled release studies revealed that the diffusion of methylene blue was influenced by the pH of buffer solution with 19.44% of MB released at pH 7.34 within 48 h indicating the potential of CMSP hydrogel nanofibers to be used as a drug carrier for MB.